Aperçu biologique du Platypus cylindrus (Fabricius, 1792) (Coleoptera, Curculionidae : Platypodinae) dans les galeries du bois de chêne-liège (Quercus suber L.) - Belhoucine, Latifa; Bouhraoua, Rachid Tarik; Dahane, Belkheir; PUJADE-VILLAR, JULI; Tarik Bouhraoua, Rachid (Orsis: organismes i sistemes, 2011)
The study of the biology of the insect Platypus cylindrus (Fabricius, 1792) in the galleries of the wood of cork oak was studied on the level of the national forest of M’Sila, littoral Oranian with semi arid climate. For that, 3 trees strongly infested by the pest were cut down between December 2007 and July 2008. The dissection of the 14 wood discs having a volume of 53 dm3 , enabled us to count 2920 individuals with an average density of 55 individuals/dm3 . At any time of the year, at least two stages of each population coexist together with fluctuating rates. The adult insects as well as the larvae are present throughout the period of experimentation. These last constitute the majority of the taken population (78%). The eggs and the nymphs, almost absent for wintry time appear in spring. Some morphological characteristics of larvae and eggs are set.
Keywords: Algeria.; biology; Cork oak; forest of M’Sila; Platypus cylindrus